2008
DOI: 10.1266/ggs.83.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the Neurospora crassa RAD14 homolog mus-43 and the RAD10 homolog mus-44 reveals that they belong to the mus-38 pathway of two nucleotide excision repair systems

Abstract: Genetic analysis of the Neurospora crassa RAD14 homolog mus-43 and the RAD10 homolog mus-44 reveals that they belong to the mus-38 pathway of two nucleotide excision repair systemsMasahito Sato, Takaharu Niki, Takeru Tokou, Kouhei Suzuki, Makoto Fujimura and Akihiko Ichiishi * Sciences, Toyo University, Itakura, Oura-gun, Gunma 374-0193, Japan (Received 30 October 2007, accepted 19 November 2007 Saccharomyces cerevisiae Rad14 and Rad10 proteins are essential for nucleotide excision repair (NER). Rad14 is a U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…These results indicate that most of the CPD repair activity during photoreactivation for 60 min depends on the photolyase. These results, together with a previous report (Sato et al, 2008), suggested that some cause of functional loss of MUS-44 protein resulted in the PPD phenotype.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…These results indicate that most of the CPD repair activity during photoreactivation for 60 min depends on the photolyase. These results, together with a previous report (Sato et al, 2008), suggested that some cause of functional loss of MUS-44 protein resulted in the PPD phenotype.…”
Section: Resultssupporting
confidence: 82%
“…1B). These results were similar to mutants produced by repeat-induced point mutation (Sato et al, 2008). Furthermore, to evaluate the photoreactivation ability of these strains, a photoreactivation assay was performed in which conidia were irradiated with visible light for 60 min after irradiation with UV light of each dose.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…265], deficiencies of other proteins do not change its activity or even reduce it [68,165,188,227,262]. Deficiencies in the BER, MMR and DRR pathways seem to increase the cytotoxicity of hydroxyurea [158,235,266], and defects in NER, FA and TLS do not seem to have a marked effect in its cytotoxicity [267][268][269]. With regard to the other drugs compiled in Table 7, deficiencies in BER increase the cytotoxicity of bortezomib and tretitoin [270][271][272] and decrease that of L-asparaginase [273], deficiencies in NER increase the cytotoxicity of arsenic trioxide [274,275] but decrease that of thalidomide [276], and deficiencies in MMR do not modify the cytotoxicity of L-asparaginase and vorinostat [277,278].…”
Section: Other Anticancer Drugsmentioning
confidence: 99%